2021
DOI: 10.1371/journal.pone.0255188
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity study of the Spanish adaptation of the “Student Satisfaction and Self-Confidence in Learning Scale” (SCLS)

Abstract: The European Higher Education Area (EHEA) recommends the use of new educational methodologies and the evaluation of student satisfaction. Different instruments have been developed in Spain to evaluate different aspects such as clinical decisions and teamwork, however no instruments have been found that specifically evaluate student self-confidence and satisfaction during clinical simulation. The aim was to translate the Student Satisfaction and Self-Confidence in Learning Scale (SCLS) questionnaire into Spanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
0
9
0
2
Order By: Relevance
“…Students' satisfaction showed a moderate and positive correlation with self-confidence in both simulation-oriented pre-clinical practice and clinical practice among nursing students (Oanh et al, 2021). Other studies have also reported a positive correlation between the levels of students' self-confidence and their satisfaction, which also positively influences their performance (Almeida et al, 2015;Farrés-Tarafa et al, 2021).…”
Section: Discussionmentioning
confidence: 90%
“…Students' satisfaction showed a moderate and positive correlation with self-confidence in both simulation-oriented pre-clinical practice and clinical practice among nursing students (Oanh et al, 2021). Other studies have also reported a positive correlation between the levels of students' self-confidence and their satisfaction, which also positively influences their performance (Almeida et al, 2015;Farrés-Tarafa et al, 2021).…”
Section: Discussionmentioning
confidence: 90%
“…Saarikoski and Leino-Kilpi (2002) developed the Clinical Learning Environment and Supervision scale (CLES-2002), whose aim is established in six factors: learning scope, supervisor leadership, service environment, characteristics of care, characteristics of learning, and relationship with the tutor [ 12 ]. In the scope of clinical simulation, Farrés-Tarafa et al (2021) have recently developed an adaptation for Spanish nursing students, by validating the Student Satisfaction and Self-Confidence in Learning Scale (SCLS) [ 13 ]. The authors concluded that clinical simulations help the students to increase their levels of confidence and satisfaction, allowing them to face real scenarios in the clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…The SCLS measures the level of satisfaction and self-confidence of nursing students in clinical simulation. The score is directly related to self-confidence without a cut-off point, indicating that higher scores are accountable for a higher self-confidence of the students [ 13 ]. Finally, a 10-item questionnaire dedicated to assessing the degree of acquisition of knowledge obtained by the students in the field of BLS in pregnant women was included, using the latest indications on BLS from the European Resuscitation Council (ERC) 2021 [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is essential to understand the needs of the student body [ 11 , 12 ]. Thus, different tools, including the Student Satisfaction and Self-Confidence in Learning Scale (SCLS), have been developed to measure student satisfaction and self-confidence through high-fidelity simulations [ 13 ]. Furthermore, these tools provide information about which factors are associated with a low level of self-confidence in students and, therefore, how they may be acted upon, improving learning results and improving the students’ learning experience in the clinical environment.…”
Section: Introductionmentioning
confidence: 99%